Targeting XBP1 mRNA splicing sensitizes glioblastoma to chemotherapy - Amiee Dowdell; Mark Marsland; Sam Faulkner; Craig Gedye; James Lynam; Cassandra P. Griffin; Joanne Marsland; Chen Chen Jiang; Hubert Hondermarck (FASEB BioAdvances, 2023)
Abstract Glioblastoma (GBM) is the most frequent and deadly primary brain tumor in adults. Temozolomide (TMZ) is the standard systemic therapy in GBM but has limited and restricted efficacy. Better treatments are urgently needed. The role of endoplasmic reticulum stress (ER stress) is increasingly described in GBM pathophysiology. A key molecular mediator of ER stress, the spliced form of the transcription factor x‐box binding protein 1 (XBP1s) may constitute a novel therapeutic target; here we report XBP1s expression and biological activity in GBM. Tumor samples from patients with GBM (n = 85) and low‐grade glioma (n = 20) were analyzed by immunohistochemistry for XBP1s with digital quantification. XBP1s expression was significantly increased in GBM compared to low‐grade gliomas. XBP1s mRNA showed upregulation by qPCR analysis in a panel of patient‐derived GBM cell lines. Inhibition of XBP1 splicing using the small molecular inhibitor MKC‐3946 significantly reduced GBM cell viability and potentiated the effect of TMZ in GBM cells, particularly in those with methylated O6‐methylguanine‐DNA methyl transferase gene promoter. GBM cells resistant to TMZ were also responsive to MKC‐3946 and the long‐term inhibitory effect of MKC‐3946 was confirmed by colony formation assay. In conclusion, this data reveals that XBP1s is overexpressed in GBM and contributes to cancer cell growth. XBP1s warrants further investigation as a clinical biomarker and therapeutic target in GBM.